THE IMPACT OF INTERNAL CONTROL SYSTEMS ON THE FINANCIAL PERFORMANCE OF MEDIUM ENTERPRISES - Ngabrano Rodney (Uganda Christian University, 2024)
This study examines the impact of internal control systems on the financial performance of medium enterprises. Internal control systems are critical for ensuring the accuracy and reliability of financial reporting, safeguarding assets, and enhancing operational efficiency. The research explores how effective internal controls contribute to improved financial outcomes by reducing errors and fraud, increasing operational efficiency, and supporting regulatory compliance. By analyzing data from medium-sized enterprises across various industries, the study assesses the relationship between the robustness of internal control systems and key financial performance indicators such as profitability, liquidity, and financial stability. Findings suggest that well-implemented internal control systems significantly enhance financial performance by mitigating risks and optimizing resource use. The study highlights best practices for developing and maintaining effective internal controls and offers recommendations for medium enterprises seeking to leverage these systems for better financial outcomes.